The effects of postoperative targeted immunotherapy on peripheral blood cytokines and immune cell profile in lung cancer patients - Zhang, Chuang; Mo, Hongmei; Li, Min; Wang, Shuaiyan; Dou, Xiaowen; Zhang, Xiuming (Frontiers in Oncology, 2024)
Objective: Cytokines and cell subsets are important components of the tumor microenvironment.Previous research has revealed that there are differences in cytokines and cell subsets in the peripheral blood of lung cancer (LCA) patients before and after eradication. The purpose of this study is to explore the monitoring value of cytokines and cellular subpopulations as biomarkers in post-immunotherapy monitoring of patients with LCA after surgery Methods: We conducted a case-control study using double-antibody sandwich magnetic microsphere flow cytometry with immunofluorescence technology and fluorescent monoclonal antibody multiparameter flow cytometry to detect differences in peripheral blood cytokines and cell subsets between LCA patients after immunotherapy and healthy controls.Results: Our research results show that there are differences in the levels of IL-4, IL-6, IL-10, IL-17, IFN-γ, TNF-α in the peripheral blood of LCA patients (n=70) after immunotherapy compared to the healthy controls (n=55) (P<0.05), and there are differences in 10 cell subgroups including DP T Cells, AT cells, and NLR in the peripheral blood compared to the healthy controls (n=35) (P<0.05). Further analysis revealed significant differences in the detection data of IL-6, IL-10, IFN-γ, CD56 dim NK cells, Total B cells, Total NE cells, CD15 + M cells, and NLR between LCA deceased patients (n=25) and LCA surviving patients (n=27) during the same period (P<0.05). The continuous monitoring of cytokines and cell subsets is far more valuable than a single-time test, as abnormal fluctuations in the data of cytokines and cell subsets are often associated with poor prognosis. In addition, IL-6 and NLR showed the strongest discriminative ability between postoperative immunotherapy-treated LCA patients and healthy controls, with AUC values of 0.840 and 0.822, respectively. There was a significant association between IFN-γ and distant metastasis in LCA(P<0.05), as well as between CD56 dim NK cells and lymph node infiltration(P<0.05).This research results support peripheral blood cytokines and cell subsets as biomarkers for monitoring the postoperative immune status and predicting the prognosis of LCA patients after immunotherapy. The continuous monitoring of cytokines and cell subsets is far more valuable than a single-time detection.